High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

Meet me in the middle: potential collaborative benthic hunting in humpback whales (Megaptera novaeangliae) - David N. Wiley; David E. Cade; Ari S. Friedlaender; Jeremy Goldbogen; Jessica Kendall-Bar; Susan E. Parks; Michael A. Thompson; Mason Weinrich; Tammy L. Silva (Behavioral Ecology and Sociobiology, 2026)
Cooperative hunting, in its numerous forms, has implications for animal cognition and social evolution. We used multi-sensor acoustic/video recording tags attached to free-swimming humpback whales (Megaptera novaeangliae) to provide the species’ first documentation of cooperative, coordinated benthic hunting and evidence supporting collaboration, the most cognitively complex level of hunting. Collaborative hunting, consisting of the tagged whale and 1–3 co-hunters, comprised 79% ( n = 110) of observed benthic-hunting events. Hunting animals concurrently arrived at the seafloor and simultaneously moved towards co-hunters, forming a head-to-head configuration that terminated when rostrums were within meters of each other; a behavior that could be seen to drive/corral sand lance ( Ammodytes dubius ) prey towards co-hunter(s). Tagged animals changed their direction of attack for each event, but co-hunters typically realigned into the same relative position, based on that of co-hunters. Using a clock position method, in relation to the tagged animal’s heading (12:00; n = 87), co-hunters occupied the 1:00 position most frequently (59%), followed by 11:00 (35%), 12:00 (12%), 3:00 (5%), and 2:00 (2%). The 1:00 and 11:00 locations would be optimal prey herding/capture positions. In events where all co-hunters were identified, individuals assumed the same position in 93.1% of events ( n = 54). Animals opened their mouths for prey capture in near unison (mean offset 3.7 s, SD 5.3 s, n = 43). The fission-fusion, non-kin-based social system of humpback whales makes them an unlikely species to evolve collaborative hunting. We speculate that the need to capture small, evasive prey, combined with cognitively driven behavioral plasticity contribute to the evolution of this hunting strategy.

A Proposed Novel Neurovascular Mechanism for Brain Network Dysfunction After Traumatic Injury - Taotao Wu; Jared A. Rifkin; Adam C. Rayfield; Keith A. Kroma-Wiley; Dani S. Bassett; David F. Meaney (Annals of Biomedical Engineering, 2026)
Current research in predicting traumatic brain injury risk focuses on the relationship between head impacts and the likelihood of white matter damage, often overlooking the role of neurovascular coupling in the injury response. To fill this gap, we combined biomechanical and neurodynamic principles to simulate alterations to large-scale resting-state brain activity following head impacts. We simulated cortical neural activity with a network of Kuramoto phase oscillators, using structural connectivity to define coupling and a vascular-informed local resource term to capture neurovascular coupling. By combining the neurodynamic model with a brain mechanics model, we investigated two mechanistic pathways of network dysfunction: (1) white matter damage, reflected in degrading network edges, and (2) local tissue oxygenation decline, reflected in adjusting the resource term at each network node. We simulated 53 real-world head impacts using a vasculature template to evaluate the changes in simulated functional connectivity (FC) and neural dynamics relative to injury outcomes (concussion vs. no concussion). To assess vascular variability, simulations were repeated across 41 individual vasculature maps. Our results show simulated FC changes (measured by Pearson’s correlation) consistently correlated well with injury outcomes, regardless of injury mechanism (AUC = 0.89 and 0.90), However, the two injury models yielded distinct FC patterns as indicated by graph metrics. Vascular variability substantially influenced how injury affected FC, with some brains exhibiting resilience to synchrony disruption depending on their vascular structure. These findings offer testable insight into the neurovascular mechanism of brain dysfunction after TBI and have important implications for individualized protection and treatment.

Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Investigating spatial overlap between northern sand lance (Ammodytes dubius) and Atlantic cod (Gadus morhua) with video trawl technology - Tammy L. Silva; Tabitha Breault; Travis M. Lowery; Nicholas M. Calabrese; Kevin D.E. Stokesbury; David N. Wiley; Gavin Fay (Fisheries Research, 2023)

Philopatry influences the genetic population structure of the blacktip shark ( Carcharhinus limbatus ) at multiple spatial scales - Dominic G. Swift; Shannon J. O'Leary; R. Dean Grubbs; Bryan S. Frazier; Andrew T. Fields; Jayne M. Gardiner; J. Marcus Drymon; Dana M. Bethea; Tonya R. Wiley; David S. Portnoy (Molecular Ecology, 2023)
Understanding how interactions among microevolutionary forces generate genetic population structure of exploited species is vital to the implementation of management policies that facilitate persistence. Philopatry displayed by many coastal shark species can impact gene flow and facilitate selection, and has direct implications for the spatial scales of management. Here, genetic structure of the blacktip shark ( Carcharhinus limbatus ) was examined using a mixed‐marker approach employing mitochondrial control region sequences and 4339 SNP‐containing loci generated using ddRAD‐Seq. Genetic variation was assessed among young‐of‐the‐year sampled in 11 sites in waters of the United States in the western North Atlantic Ocean, including the Gulf of Mexico. Spatial and environmental analyses detected 68 nuclear loci putatively under selection, enabling separate assessments of neutral and adaptive genetic structure. Both mitochondrial and neutral SNP data indicated three genetically distinct units—the Atlantic, eastern Gulf, and western Gulf—that align with regional stocks and suggest regional philopatry by males and females. Heterogeneity at loci putatively under selection, associated with temperature and salinity, was observed among sites within Gulf units, suggesting local adaptation. Furthermore, five pairs of siblings were identified in the same site across timescales corresponding with female reproductive cycles. This indicates that females re‐used a site for parturition, which has the potential to facilitate the sorting of adaptive variation among neighbouring sites. The results demonstrate differential impacts of microevolutionary forces at varying spatial scales and highlight the importance of conserving essential habitats to maintain sources of adaptive variation that may buffer species against environmental change.

Age, Growth and Maturity of the Bonnethead Sphyrna tiburo in the U.S. Gulf of Mexico - Bryan S. Frazier; Elizabeth A. Vinyard; Andrew T. Fields; William B. Driggers; R. Dean Grubbs; Douglas H. Adams; J. Marcus Drymon; Jayne M. Gardiner; Jill M. Hendon; Eric Hoffmayer; Robert E. Hueter; R. J. David Wells; et al. (Environmental Biology of Fishes, 2023)

Age-Related Interactions with Wind During Migration Support the Hypothesis of Developmental Learning in a Migrating Long-Lived Seabird - Kevin D. Powers; Isabeau Pratte; Robert A. Ronconi; Sarah N. P. Wong; Peter G. Ryan; Linda J. Welch; Tammy L. Silva; Kent A. Hatch; Andrew J. Westgate; David N. Wiley (Frontiers in Marine Science, 2022)
Wind patterns shape migratory pathways and detours of many procellariiform bird species that seasonally migrate between hemispheres. These seabirds are long-lived, and the period of immaturity is presumed to be a time of development and learning the environment, specifically how to use wind to their advantage. We assess how wind encountered by individual Great Shearwaters ( Ardenna gravis ) varies along the migration journey and compare responses between presumed mature and immature birds (early and late, respectively) in southbound migration and mature birds in northbound migration. We analyze modeled Argos locations from 71 individual tracks of migratory Great Shearwaters with concurrent U (East/West) and V (North/South) wind components. Migration in seabirds is well studied, but there is limited quantitative work measuring individual birds directly interacting with wind and their associated changes in flight behavior during migration. We show that Great Shearwaters made optimal use of winds, and that different age groups made decisions that exposed them to different wind constraints. Overall, Great Shearwaters derived positive responses from wind under most conditions and did not rely on a drifting strategy, which would be suggested if wind effect (difference between ground and airspeed) was predominantly positive during migrations. Instead, they appeared to use a compensating strategy to achieve an acceptable course and speed. The difference we observed in migration phenologies suggests that by migrating later, immature birds might travel the path of least resistance and experience flight conditions that are less risky furthering their ability to withstand a variety of wind conditions encountered later in life as done by adults, which migrate earlier and are subject to more variable flight conditions. We conclude that like other procellariiforms, a longer period of sexual maturity is required to enhance flight performance and mediate energy expenditure through experiential learning and increased fitness.

The effect of group size on individual behavior of bubble‐net feeding humpback whales in the southern Gulf of Maine - Natalie C. Mastick; David Wiley; David E. Cade; Colin Ware; Susan E. Parks; Ari S. Friedlaender (Marine Mammal Science, 2022)
In many species, group foraging is a strategy used to increase the efficiency of individuals to find and exploit patchy prey. Humpback whales ( Megaptera novaeangliae ) are one of the few baleen whale species reported to use coordinated foraging strategies. One of these behaviors, bubble‐net feeding, has been observed in several populations, though the behaviors of individuals within these groups are largely unknown. This study used multisensor kinematic tag data from 26 whales foraging in the Southern Gulf of Maine to analyze individual bubble‐net feeding behaviors. Linear mixed effects models were used to test if there were differences in individual whales' dive behaviors across group size. The results indicate that individuals performed consistent bubble‐net feeding behaviors regardless of the size of their foraging group, except when using one specific foraging behavior, the upward spiral. Overall complexity of foraging dives, based on the three‐dimensional movements of the dive, decreased with increasing group size when group members used upward spirals. This may indicate that in larger groups, participants in coordinated feeding events need to move less and expend less energy to corral prey. This study provides new insights into the effects of group size on individual behavior and group coordination in humpback whales.

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Larval transport pathways from three prominent sand lance habitats in the Gulf of Maine - Justin J. Suca; Rubao Ji; Hannes Baumann; Kent Pham; Tammy L. Silva; David N. Wiley; Zhixuan Feng; Joel K. Llopiz (Fisheries Oceanography, 2022)
Northern sand lance ( Ammodytes dubius ) are among the most critically important forage fish throughout the Northeast US shelf. Despite their ecological importance, little is known about the larval transport of this species. Here, we use otolith microstructure analysis to estimate hatch and settlement dates of sand lance and then use these measurements to parametrize particle tracking experiments to assess the source–sink dynamics of three prominent sand lance habitats in the Gulf of Maine: Stellwagen Bank, the Great South Channel, and Georges Bank. Our results indicate the pelagic larval duration of northern sand lance lasts about 2 months (range: 50–84 days) and exhibit a broad range of hatch and settlement dates. Forward and backward particle tracking experiments show substantial interannual variability, yet suggest transport generally follows the north to south circulation in the Gulf of Maine region. We find that Stellwagen Bank is a major source of larvae for the Great South Channel, while the Great South Channel primarily serves as a sink for larvae from Stellwagen Bank and Georges Bank. Retention is likely the primary source of larvae on Georges Bank. Retention within both Georges Bank and Stellwagen Bank varies interannually in response to changes in local wind events, while the Great South Channel only exhibited notable retention in a single year. Collectively, these results provide a framework to assess population connectivity among these sand lance habitats, which informs the species' recruitment dynamics and impacts its vulnerability to exploitation.

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

Sherri Eldridge 1959–2020 - Richard C. Connor; Darlene R. Ketten; Michael J. Moore; Joy S. Reidenberg; Douglas L. Rosene; Tammy Silva; David N. Wiley (Marine Mammal Science, 2021)

Complete genomic sequences of Venezuelan equine encephalitis virus subtype IIID isolates from mosquitoes - Susana L. Padilla; Karla Prieto; David J. Dohm; Michael J. Turell; Terry A. Klein; Roberto Fernández; Douglas M. Watts; Robert G. Lowen; Gustavo F. Palacios; Margaret L. Pitt; Michael R. Wiley; Farooq Nasar (Archives of Virology, 2020)

The role of sand lances ( Ammodytes sp.) in the Northwest Atlantic Ecosystem: A synthesis of current knowledge with implications for conservation and management - Michelle D. Staudinger; Holly Goyert; Justin J. Suca; Kaycee Coleman; Linda Welch; Joel K. Llopiz; David Wiley; Irit Altman; Andew Applegate; Peter Auster; Hannes Baumann; Julia Beaty; et al. (Fish and Fisheries, 2020)
The American sand lance ( Ammodytes americanus , Ammodytidae) and the Northern sand lance ( A. dubius , Ammodytidae) are small forage fishes that play an important functional role in the Northwest Atlantic Ocean (NWA). The NWA is a highly dynamic ecosystem currently facing increased risks from climate change, fishing and energy development. We need a better understanding of the biology, population dynamics and ecosystem role of Ammodytes to inform relevant management, climate adaptation and conservation efforts. To meet this need, we synthesized available data on the (a) life history, behaviour and distribution; (b) trophic ecology; (c) threats and vulnerabilities; and (d) ecosystem services role of Ammodytes in the NWA. Overall, 72 regional predators including 45 species of fishes, two squids, 16 seabirds and nine marine mammals were found to consume Ammodytes . Priority research needs identified during this effort include basic information on the patterns and drivers in abundance and distribution of Ammodytes , improved assessments of reproductive biology schedules and investigations of regional sensitivity and resilience to climate change, fishing and habitat disturbance. Food web studies are also needed to evaluate trophic linkages and to assess the consequences of inconsistent zooplankton prey and predator fields on energy flow within the NWA ecosystem. Synthesis results represent the first comprehensive assessment of Ammodytes in the NWA and are intended to inform new research and support regional ecosystem‐based management approaches.

Response of small sharks to nonlinear internal waves - Jesús Pineda; Sally Rouse; Victoria Starczak; Karl Helfrich; David Wiley (Limnology and Oceanography, 2020)
Plankton and nekton may respond passively or actively to large‐amplitude, nonlinear internal waves (NLIW), with periods and wavelengths on the order of minutes and hundreds of meters, and the NLIW can cause direct or indirect changes in distribution. NLIW are ubiquitous in the coastal ocean, but understanding the influence of NLIW on organism response and distribution is challenging, because of NLIW unpredictability, short temporal and spatial scales, and the difficulty in resolving the biological response. Measurements of currents, temperature, and shark acoustic traces in Massachusetts Bay were used to evaluate the short‐term response of individuals as well as the mean effects on the distribution of an aggregation of small sharks, Squalus acanthias . In two NLIW events, we detected 527 and 3240 shark traces. Individuals moved up and down in response to the currents associated with the sinking and rising of the thermocline. However, mean distribution deepened during one of the events, suggesting that organisms did not merely move in concert with the thermocline oscillation, but that sharks instead might have responded actively. Measurements of vertical currents and shark's depth change during one of the NLIW events indicate that with downward currents (sinking of the thermocline), the sharks tend to react passively. However, in response to the fastest upward currents, sharks appeared to swim down, supporting an active response in the rising phase of the wave. NLIW and other high‐frequency processes can have a profound influence on the distribution of pelagic organisms, yet their ecological consequences remain largely unaccounted for.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

The Mini Report: a Practical Tool to Address Lung Cancer Disparities in Rural Communities - Georgia S. Mueller-Luckey; Whitney E. Zahnd; Kyle Garner; Ruth Heitkamp; Wiley D. Jenkins; Michael D. Boehler; David E. Steward (Journal of Cancer Education, 2017)

Vessel strike mitigation lessons from direct observations involving two collisions between noncommercial vessels and North Atlantic right whales ( Eubalaena glacialis ) - David N. Wiley; Charles A. Mayo; Eden Marie Maloney; Michael J. Moore (Marine Mammal Science, 2016)

Bottom side‐roll feeding by humpback whales ( Megaptera novaeangliae ) in the southern Gulf of Maine, U.S.A - Colin Ware; David N. Wiley; Ari S. Friedlaender; Mason Weinrich; Elliott L. Hazen; Alessandro Bocconcelli; Susan E. Parks; Alison K. Stimpert; Mike A. Thompson; Kyler Abernathy (Marine Mammal Science, 2014)
Humpback whales (Megaptera novaeangliae) are known for the variety and complexity of their feeding behaviors. Here we report on the use of synchronous motion and acoustic recording tags ( DTAG s) to provide the first detailed kinematic descriptions of humpback whales using bottom side‐rolls ( BSR s) to feed along the seafloor. We recorded 3,505 events from 19 animals (individual range 8–722). By animal, mean BSR duration ranged from 14.1 s to 36.2 s.; mean body roll angle from 80º to 121º, and mean pitch from 7º to 38º. The median interval between sequential BSR s, by animal, ranged from 24.0 s to 63.6 s and animals tended to maintain a consistent BSR heading during long BSR series encompassing multiple dives. BSR s were most frequent between 2200 and 0400. We identify three classes of behavior: simple side‐roll, side‐roll inversion, and repetitive scooping. Results indicate that BSR feeding is a common technique in the study area and there is both coordination and noncoordination between animals. We argue that this behavior is not lunge feeding as normally characterized, because animals are moving slowly through the event. The behavior also leads to vulnerability to entanglement in bottom‐set fishing gear, a major mortality factor for the species.

Foraging segregation and genetic divergence between geographically proximate colonies of a highly mobile seabird - Anne E. Wiley; Andreanna J. Welch; Peggy H. Ostrom; Helen F. James; Craig A. Stricker; Robert C. Fleischer; Hasand Gandhi; Josh Adams; David G. Ainley; Fern Duvall; Nick Holmes; Darcy Hu; et al. (Oecologia, 2012)

Erratum to: Characterizing the Relative Contributions of Large Vessels to Total Ocean Noise Fields: A Case Study Using the Gerry E. Studds Stellwagen Bank National Marine Sanctuary - Leila Hatch; Christopher Clark; Richard Merrick; Sofie Van Parijs; Dimitri Ponirakis; Kurt Schwehr; Michael Thompson; David Wiley (Environmental Management, 2009)

Characterizing the Relative Contributions of Large Vessels to Total Ocean Noise Fields: A Case Study Using the Gerry E. Studds Stellwagen Bank National Marine Sanctuary - Leila Hatch; Christopher Clark; Richard Merrick; Sofie Van Parijs; Dimitri Ponirakis; Kurt Schwehr; Michael Thompson; David Wiley (Environmental Management, 2008)

Landscape based identification of human disturbance gradients and reference conditions for Michigan streams - Lizhu Wang; Travis Brenden; Paul Seelbach; Arthur Cooper; David Allan; Richard Clarck; Michael Wiley (Environmental Monitoring and Assessment, 2008)

Landscape Based Identification of Human Disturbance Gradients and Reference Conditions for Michigan Streams - Lizhu Wang; Travis Brenden; Paul Seelbach; Arthur Cooper; David Allan; Richard Clark; Michael Wiley (Environmental Monitoring and Assessment, 2008)

Effectiveness of Voluntary Conservation Agreements: Case Study of Endangered Whales and Commercial Whale Watching - DAVID N. WILEY; JUST C. MOLLER; RICHARD M. PACE; CAROLE CARLSON (Conservation Biology, 2008)
The use of voluntary approaches to achieve conservation goals is becoming increasingly popular. Nevertheless, few researchers have quantitatively evaluated their efficacy. In 1998 industry, government agencies, and nongovernmental organizations established a voluntary conservation program for whale watching in the northeast region of the United States, with the intent to avoid collisions with and harassment of endangered whales by commercial and recreational whale‐watching vessels. One important aspect of the program was the establishment of 3 speed zones within specific distances of whales. We wanted to determine the level of compliance with this aspect of the program to gauge its efficacy and gain insights into the effectiveness of voluntary measures as a conservation tool. Inconspicuous observers accompanied 46 commercial whale‐watching trips from 12 companies in 2003 (n= 35) and 2004 (n= 11). During each trip, vessel position and speed were collected at 5‐second intervals with a GPS receiver. Binoculars with internal laser rangefinders and digital compasses were used to record range and bearing to sighted whales. We mapped whale locations with ArcGIS. We created speed‐zone buffers around sighted whales and overlaid them with vessel‐track and speed data to evaluate compliance. Speeds in excess of those recommended by the program were considered noncompliant. We judged the magnitude of noncompliance by comparing a vessel's maximum speed within a zone to its maximum recorded trip speed. The level of noncompliance was high (mean 0.78; company range 0.74–0.88), some companies were more compliant than others (p= 0.02), noncompliance was significantly higher in zones farther from whales (p .

Quantity versus Quality in California Condor Reintroduction: Reply to Beres and Starfield - Vicky Meretsky; Noel F. R. Snyder; Steven R. Beissinger; David A. Clendenen; James W. Wiley (Conservation Biology, 2001)

Quantity versus Quality in California Condor Reintroduction: Reply to Beres and Starfield - Vicky Meretsky; Noel F. R. Snyder; Steven R. Beissinger; David A. Clendenen; James W. Wiley (Conservation Biology, 2001)

Demography of the California Condor: Implications for Reestablishment - Vicky J. Meretsky; Noel F. R. Snyder; Steven R. Beissinger; David A. Clendenen; James W. Wiley (Conservation Biology, 2000)
The remnant wild population of California Condors ( Gymnogyps californianus ) of the 1980s exhibited a rapid population decline caused by high mortality rates among adult and immature birds. The most prominent mortality factor was lead poisoning resulting from ingestion of bullet fragments in carcasses. Successful captive breeding has allowed many birds to be released to the wild since 1992, based originally on an assumption that exposure to lead could be prevented by food subsidy. The mortality of released birds, however, has generally exceeded levels needed for population stability calculated from simple population models. Collision with overhead wires was the most frequent cause of death in releases before 1994. Lead poisoning again surfaced as a problem starting in 1997 as older birds began feeding on carcasses outside the subsidy program. Although poisonings have been treated successfully by chelation therapy in recaptured birds, food subsidy is proving an ineffective solution to lead exposure. The best long‐term solution appears to be either the creation of large reserves where hunting is prohibited or the restriction of hunting to nontoxic ammunition in release areas. Until sources of lead contamination are effectively countered, releases cannot be expected to result in viable populations. In addition, problems involving human‐oriented behavior have resulted in the permanent removal of many released birds from the wild. The most promising reduction in human‐oriented behavior has been achieved in one release of aversively conditioned, parent‐reared birds. Rigorous evaluation of the factors reducing attraction to humans and human structures has been hampered by confounding of techniques in releases. Behavioral problems could be more quickly overcome by adoption of a comprehensive experimental approach.

Harnessing Museum Resources for the Census of Marine Life: The FISHNET Project - David Vieglais; E.O. Wiley; Richard Robins; Townsend Peterson (Oceanography, 2000)

The use of genetic markers to estimate the frequency of successful alternative reproductive tactics - David F. Westneat; Peter C. Frederick; R. Haven Wiley (Behavioral Ecology and Sociobiology, 1987)